Answer:
![(x,y)=\left(\; \boxed{-3,2} \; \right)\quad \textsf{(smaller $x$-value)}](https://img.qammunity.org/2023/formulas/mathematics/college/mdc25n4ms39nrgc62fifw6ew2qiubgf8yw.png)
![(x,y)=\left(\; \boxed{1,0} \; \right)\quad \textsf{(larger $x$-value)}](https://img.qammunity.org/2023/formulas/mathematics/college/2r7yu9rrun2g2kei50zbppetycsamf4n03.png)
Explanation:
Given system of equations:
![\begin{cases}\;\;\;\;\;\;\;y^2=1-x\\x+2y=1\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/zi7s9560g282g2wiegpe26py1vtlhhn5ud.png)
To solve by the method of substitution, rearrange the second equation to make x the subject:
![\implies x=1-2y](https://img.qammunity.org/2023/formulas/mathematics/college/i807ibbkxsqivzdl1uu78u4cyn942se57w.png)
Substitute the found expression for x into the first equation and rearrange so that the equation equals zero:
![\begin{aligned}x=1-2y \implies y^2&=1-(1-2y)\\y^2&=1-1+2y\\y^2&=2y\\y^2-2y&=0\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/5ayrwgn1h076nd4eznkb3whibyboyvbof2.png)
Factor the equation:
![\begin{aligned}\implies y^2-2y&=0\\y(y-2)&=0\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/5sk69uti18gzcvwlhw1t81egm1af3uxhft.png)
Apply the zero-product property and solve for y:
![\implies y=0](https://img.qammunity.org/2023/formulas/mathematics/college/xp4vl9uok5cge84vo6cu98qbav6cof9m2z.png)
![\implies y-2=0 \implies y=2](https://img.qammunity.org/2023/formulas/mathematics/college/cn0975heg76z8q90c87t9rxp3r9wjecgin.png)
Substitute the found values of y into the second equation and solve for x:
![\begin{aligned}y=0 \implies x+2(0)&=1\\x&=1\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/b9owrihuo7n1ssbe4if0dtyczi8rs2vdto.png)
![\begin{aligned}y=2 \implies x+2(2)&=1\\x+4&=1\\x&=-3\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/8at270fg1nskj9ggbctgozx1jp649nowqy.png)
Therefore, the solutions are:
![(x,y)=\left(\; \boxed{-3,2} \; \right)\quad \textsf{(smaller $x$-value)}](https://img.qammunity.org/2023/formulas/mathematics/college/mdc25n4ms39nrgc62fifw6ew2qiubgf8yw.png)
![(x,y)=\left(\; \boxed{1,0} \; \right)\quad \textsf{(larger $x$-value)}](https://img.qammunity.org/2023/formulas/mathematics/college/2r7yu9rrun2g2kei50zbppetycsamf4n03.png)